Audio-Assisted Smartbox Learning Media in IPAS Content of Metamorphosis of Animals for Fourth-Grade Students - Failasufah, Meilia; Setyasto, Novi (LPPM Undiksha, 2023)
One of the prevalent issues faced by students in the IPAS subject is the utilization of monotonous media, resulting in lower learning outcomes. This research aims to develop and evaluate the feasibility and effectiveness of SmartBox media assisted by audio for the IPAS subject, specifically focusing on the topic of animal life cycles. Employing the Borg and Gall method, this study falls under the category of research and development with the research sample consisting of 27 students. The data collection techniques encompassed observation, interviews, tests, questionnaires, and document analysis. The evaluation results from expert validators in both content and media fields revealed scores of 98% and 92%, respectively, indicating a highly suitable categorization. Moreover, the media garnered positive responses from both students and teachers. Additionally, the developed media demonstrated its effectiveness in enhancing learning outcomes, as evidenced by a t-test result with a Sig. value of 0.000, indicating a significant difference between pretest and post-test data. This finding is supported by an n-gain score of 0.44, classified as moderate, signifying an increase in the average results of pretest and post-test using the audio-assisted SmartBox learning media. In conclusion, the SmartBox learning media with audio assistance for the IPAS subject on animal life cycles is deemed highly appropriate, effective, and valid for implementation in the teaching process, as it effectively improves student learning outcomes.